ANALYZING THE CAUSE OF TIDAL FLOODING IN RANDUSANGA KULON VILLAGE, BREBES DISTRICT, BREBES REGENCY - Barkah, Atiyah (International Journal of Engineering Technologies and Management Research, 2024)
In Indonesia, many regions experienced inundation as a result of the rise of seawater. One of them is the coast of Randusanga Kulon village. The coastal area of Randusanga Kulon village has recreation spots and ponds. These areas are located at the edge of a river estuary which is directly adjacent to the sea. On the other hand, the settlement area is located just 3 km from the seaside. Therefore, when a high tide occurs, the recreation, pond, and settlement areas will be hit by tidal floods. This study aimed to analyze the causes and impacts of tidal floods that hit Randusanga Kulon Village of Brebes District of Brebes Regency. The methods used to process the data are the Formzahl and Admiralty methods. The result of calculating using the admiralty method is that Brebes Sea has Mixed Semi-Diurnal type of daily tides with a Formzahl value of 0,9948. The value of HHWL was calculated to determine the prediction of seawater rise. By using the Admiralty Method the result is 47 cm, and by using SLR data due to global warming, it is 30 cm.